Analysis of User Complaints for Telecommunication Brands on X (Twitter) using IndoBERT and Deep Learning - Hakim, Valianda Farradillah; Riana, Dwiza (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2024)
Tweeting on different official accounts is what users of Twitter (X) do most frequently. These tweets ranging from compliments to critiques. One of the official accounts that gets a lot of tweets from its customers is Telkomsel, an Indonesian telecom company. This study aims to find the maximum accuracy that can be obtained by combining CNN and Bi-LSTM algorithms with IndoBERT embeddings. A considerable accuracy level above 90% is demonstrated by the study, with CNN obtaining the greatest accuracy of 99% at a learning rate of 6*10^-5, along with scores of 98%, 97%, and 97% for precision, recall, and F1 correspondingly.